Can PEM Fuel Cells Experience Appreciable Degradation at Short Circuit?1. Issue 2 (1st June 2016) - Bonnet, C.; Lapicque, F.; Belhadj, M.; Gerardin, K.; Raël, S.; Hinaje, M.; Mitchell, L.; Goldsmith, V.; Kmiotek, S. J.
Abstract: Operation of PEM fuel cells at very low voltages can occur in the case of direct hybridization with supercapacitors, depending on their charge level: in such cases, the cell acts as reliable current sources that can be used with low voltage devices. In spite of the growing importance of this electrical mode aging phenomena for such conditions are still unknown. A single 100 cm 2 cell was operated for more than 2, 000 hours at short circuit. The current delivered by the cell provided with an MEA after suitable maturation, was shown to be approx. 98% of that corresponding to the injected hydrogen flow rate. The state‐of‐health of the cell was followed by impedance measurements and determination of the electrochemical surface area of the cathode and the fuel crossover. Significant, regular decay rate of the cell voltage after the low‐voltage run was observed to range from 30 to 100 µV h −1 depending on the current density. The features of the cell were little‐to‐moderately affected by the particular regime: 43% of ECSA was lost which affects only little the FC performance, and hydrogen crossover remains unchanged. Only the diffusion resistance was increased up to fourfold at high current density.